CircADSS contributes to hepatocellular carcinoma development by regulating miR‐431‐5p/TOP2A. (2nd March 2023) - Gong, Jianzhuang; Du, Chenxu; Sun, Nai; Xiao, Xingguo; Wu, Huili
Abstract: CircRNAs participated in regulating hepatocellular carcinoma (HCC), and the regulation function of circRNA adenylosuccinate synthase (circADSS) on HCC development is not clear. RT‐qPCR and western blot were performed to detect RNA expression. Cell proliferation was analysed by CCK‐8 and EdU assay. Cell cycle distribution was analysed by flow cytometry assay. Cell migration and invasion were measured by transwell assay. Mechanism assays were employed to examine the interaction between miR‐431‐5p and circADSS, or TOP2A. Xenograft mouse model was constructed for in vivo assay. CircADSS and TOP2A expression were boosted, while miR‐431‐5p was limited in tumour tissues and cells. CircADSS silencing decreased HCC cell proliferation, cell cycle progression, migration, invasion, as well as EMT. MiR‐431‐5p inhibitors or ectopic TOP2A expression could restore the effect of circADSS knockdown on HCC progression. There was target relationship between miR‐431‐5p and circADSS, or TOP2A. Knockdown of circADSS suppressed tumour growth in vivo. CircADSS could regulate HCC cell malignancy by miR‐431‐5p/TOP2A axis. Abstract : CircADSS is formed by the cyclization of the exons 5–11 of the ADSS gene and its expression is upregulated in HCC tissues and cells; enforced circADSS expression induces TOP2A production by interacting with miR‐431‐5p, thus promoting HCC cell proliferation, migration and invasion.